Nghiên cứu phản ứng trùng hợp ghép hợp chất vinylic lên mạch dị vòng Polysacarit - Mai, Tuyên (Đại học Quốc gia Hà Nội, 2020)
A study on the reaction of graft polymerization of vinylic compounds onto polysaccheide was carried out using cerium ion from Vietnamese resource as initiator